Evaluation of Drug–Drug Interaction Potential between Baloxavir Marboxil and Oseltamivir in Healthy Subjects - Kawaguchi, Nao; Koshimichi, Hiroki; Ishibashi, Toru; Wajima, Toshihiro (Clinical drug investigation, 2018)
Background and Objective Baloxavir marboxil is a prodrug that is metabolized to baloxavir acid, which suppresses viral replication by inhibiting cap-dependent endonuclease with a single oral administration. As the mode of action of baloxavir marboxil is different from that of neuraminidase inhibitors, such as oseltamivir, combination treatment with these drugs can be a treatment option, particularly for severe influenza infection. The aim of this study was to assess the drug–drug interaction between baloxavir marboxil and oseltamivir. Methods Eighteen healthy adult subjects received three treatments in a crossover fashion: single administration of baloxavir marboxil 40 mg alone, repeated twice-daily administration of oseltamivir at 75 mg for 5 days, or single administration of baloxavir marboxil at 40 mg in combination with repeated twice-daily administration of oseltamivir at 75 mg for 5 days. Results The ratios (90% confidence intervals) of maximum plasma concentration and area under the plasma concentration–time curve of baloxavir acid after co-administration compared to baloxavir marboxil alone were 1.03 (0.92–1.15) and 1.01 (0.96–1.06), respectively. The ratios (90% confidence intervals) of maximum plasma concentration and area under the plasma concentration–time curve of oseltamivir carboxylate, the active form of oseltamivir, after co-administration compared to oseltamivir alone were 0.96 (0.93–1.00) and 0.99 (0.96–1.01), respectively, at steady state on day 5. Treatment-emergent adverse events reported were mild and not considered to be related to the study drug. Conclusion The lack of a clinically meaningful drug–drug interaction between baloxavir marboxil and oseltamivir has been established.